Patient-Reported Quality of Life After Breast Reconstruction. Issue 2 (August 2015) - Pinell-White, Ximena A.; Duggal, Claire; Metcalfe, Drew; Sackeyfio, Robyn; Hart, Alexandra M.; Losken, Albert
<x xml:space="preserve">Abstract</x> Background Patient-reported quality of life (QOL) is an important measure of the impact that breast reconstruction has on postmastectomy patients. This study seeks to describe psychosocial outcomes after breast reconstruction and to identify factors that influence them. Methods All patients who underwent immediate postmastectomy reconstruction by the senior author between 2009 and 2011 were offered participation in this study. Patients completed the World Health Organization QOL-BREF questionnaire preoperatively and 1-year postoperatively. Change scores were compared across reconstructive techniques, as well as across various demographic and clinical variables. Results One hundred twenty-nine women completed the preoperative questionnaire, and 60 patients completed the follow-up questionnaire at 1 year (response rate, 46.5%). Compared to the preoperative baseline, overall QOL was unchanged, general satisfaction with health improved significantly, and QOL in physical, psychological, social, and environmental domains decreased (P < 0.05 for all but social domains). On bivariate analysis, being in a relationship at the time of reconstruction was associated with a decline in overall QOL, as well as the quality of social relationships and environment. Educational level impacted how physical and psychological wellness evolved after surgery. Patients with a higher cancer stage reported a decrease in satisfaction with health at 1 year. Type of reconstruction, development of a complication, and need for additional surgery did not influence any of these outcomes. Conclusions At 1-year follow-up from postmastectomy reconstruction, breast cancer survivors report a similar overall QOL, but significant decrements in physical, psychological, and environmental QOL. Satisfaction with health improved. The type of breast reconstruction did not influence any of these outcomes.